Ether Dynamics and Unification of Gravitational and Electromagnetic forces (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: unification of gravitational and electromagnetic forces; ether dynamics; gravitation; biot-savart law; lorentz force